Economic Geography Analysis - Bundervoet, Tom (The World Bank, 2021)
This background note analyzes the economic geography of the Horn of Africa using the framework of the 2009 Word Development Report. For the purpose of this report, the Horn of Africa (henceforth HoA) comprises of five countries: Djibouti, Eritrea, Ethiopia, Kenya and Somalia. This note first seeks to provide a descriptive snapshot of recent socio-economic trends in the HoA countries vis-a-vis the regional trends in sub-Sahara Africa (SSA) as a whole. Second, it sheds light on the economic geography of the HoA region with a particular focus on 3D (density, distance, and division). Inparticular, this note highlights that borderlands of the HoA countries suffer from a combination of low density and high distance that hinders theborderlands from tapping their full economic potential. It finally concludes with a set of policy recommendations for removing barriers to sustainable growth in the region
Keywords: Economic Geography; Living Standards; Macroeconomics and Economic Growth